Assessing the Effectiveness of Employment Policies for Filipino Migrant Workers - Ballesteros, Tabios Dominic; Santos, Fernando David; Rubenito, Edwino Mudjekeewis; Angelo, Lampayan (International Journal of Law and Public Policy (IJLAPP), 2025)
The Philippines ranks among the top nations globally for labor migration, with remittances playing a vital role in the national economy. Filipino migrant workers still encounter obstacles despite their economic contributions, such as human rights abuses, hazardous working environments, and issues with reintegration. This research assesses how well Philippine labor laws and policies safeguard the rights of migrant workers and promote effective reintegration strategies. Employing a case study approach, information was gathered via the analysis of policy documents, government reports, and semi-structured interviews with 25 important informants, such as migrant workers, policymakers, and scholars. The research locations comprised Metro Manila, Cebu City, and Davao City. Results indicate that despite the Philippines having a thorough legal framework for safeguarding migrant workers, enforcement is insufficient because of resource limitations and minimal international oversight. Reintegration programs like skills training and entrepreneurship initiatives face underutilization because of accessibility challenges and social stigma. Additionally, shortcomings in legal aid and the enforcement of labor rights leave migrant workers vulnerable to exploitation. A comparison with South Korea and Singapore emphasizes effective strategies in legal safeguarding and reintegration assistance. Bolstering enforcement systems and improving cross-border legal collaboration are crucial for enhancing the welfare of migrants. Subsequent studies need to investigate the influence of technology on labor rights oversight and the lasting socio-economic effects of reintegration strategies. Tackling these challenges will strengthen legal safeguards and enhance sustainable welfare for Filipino migrant workers and their families.